Stagecoach to Denver - Springsteen, R. G., 1904-1989; Snell, Earle, 1886-1965; Lane, Allan, 1904-1973; Republic Pictures Corporation; Cinetel Films ([Los Angeles, CA] : Republic Pictures Corporation, 1946)
Lambert has the stagecoach wrecked killing the Commissioner so his phoney replacement can alter Coonskin's land survey. When Red Ryder exposes the survey hoax, Lambert has his stooge Sheriff put Red in jail. --
Originally released as a motion picture in 1946.
"Based on Fred Harman's famous Nea Comic."
Allan Lane, Bobby Blake, Martha Wentworth, Roy Barcroft, Peggy Stewart, Emmett Lynn, Ted Adams.
Cinematographer, Edgar Lyons; editor, Les Orlebeck; music, Mort Glickman.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed December 4, 2015).
Keywords: Ryder, Red -- Drama; Stagecoaches -- Drama; Impostors and imposture -- Drama; Kidnapping -- Drama; Stagecoach robberies -- Drama; Murder -- Drama; Western films; Feature films; Internet videos; Short films; Streaming video